2010
DOI: 10.4212/cjhp.v63i5.948
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Vancomycin 25 mg/mL in Ora-Sweet and Water in Unit-Dose Cups and Plastic Bottles at 4°C and 25°C

Abstract: Background: Solutions of vancomycin for oral administration are not available commercially in Canada or the United States but are needed for patients who cannot swallow capsules.Objective: To evaluate the stability of vancomycin solutions stored in unit-dose cups and plastic bottles under refrigeration (4°C) and at room temperature (25°C) for up to 75 days. Methods:Vancomycin 25 mg/mL in Ora-Sweet vehicle and water (1:1 ratio by volume) was dispensed into opaque blue polyethylene unit-dose cups with aluminum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
1
15
1
Order By: Relevance
“…However this study indicates that 0.07 mmol/L vancomycin in the bottles is enough to maintain an inhibitory effect for at least 32 days at 35°C with the wastewater-treatment sludge used. This outcome is consistent with a few clinical studies regarding vancomycin stability in storage (Das et al 1986;Ensom et al 2010), which showed that vancomycin solutions stored at 25°C could maintain at least 90% of their initial concentration for up to 30 days. Another study (Murray et al 1995) established that there were no differences in vancomycin antimicrobial potency and stability for over 1 month when kept at room temperature.…”
Section: Discussionsupporting
confidence: 92%
“…However this study indicates that 0.07 mmol/L vancomycin in the bottles is enough to maintain an inhibitory effect for at least 32 days at 35°C with the wastewater-treatment sludge used. This outcome is consistent with a few clinical studies regarding vancomycin stability in storage (Das et al 1986;Ensom et al 2010), which showed that vancomycin solutions stored at 25°C could maintain at least 90% of their initial concentration for up to 30 days. Another study (Murray et al 1995) established that there were no differences in vancomycin antimicrobial potency and stability for over 1 month when kept at room temperature.…”
Section: Discussionsupporting
confidence: 92%
“…§Calculated from lower limit of 95% CI of the slope of the curve relating concentration to time, determined by linear regression, according to the following formula: [(90% -lower limit of 95% CI of concentration at time 0) ÷ slope of 95% CI of linear regression curve). In contrast to a previous study using a lower concentration of vancomycin (25 mg/mL) in a different vehicle, 1 there was a high degree of variability in taste, subjective palatability, viscosity, and miscibility of samples prepared from both liquid and powdered vancomycin. The mean pH (± standard deviation) for both types of preparation increased over time (for liquid, pH 3.29 ± 0.017 on day 0 to 3.85 ± 0.078 on day 91; for powder, pH 3.52 ± 0.021 on day 0 to 3.96 ± 0.032 on day 91), as has been observed previously.…”
contrasting
confidence: 45%
“…Forced degradation decreased the amount of vancomycin (with base, a 91.8% decrease; with heat, a 87.8% decrease) but no changes in peak shape or retention time. Small degradation peaks were observed 1,2 ; however, there were no interfering peaks compared to controls.…”
mentioning
confidence: 98%
“…No significant changes were observed in the transfer characteristic of the biosensor. Vancomycin has also been shown to be stable at room temperature for at least 26 days in solution . This suggests that the FET device need not be stored at special temperature controlled conditions.…”
Section: Resultsmentioning
confidence: 99%